Normal meal tolerance test is preferable to the glucagon stimulation test in patients with type 2 diabetes that are not in a hyperglycemic state: Comparison with the change of C‐peptide immunoreactivity. Issue 2 (19th June 2017) - Fujioka, Youhei; Okura, Tsuyoshi; Sumi, Keisuke; Matsumoto, Kazuhisa; Shoji, Kyoko; Nakamura, Risa; Matsuzawa, Kazuhiko; Izawa, Shoichiro; Kato, Masahiko; Taniguchi, Shinichi; Yamamoto, Kazuhiro
Abstract: Aims/Introduction: The aim of the present study was to evaluate the properties of the glucagon stimulation test (GST) and the normal meal tolerance test (NMTT) in patients with type 2 diabetes. Materials and Methods: We enrolled 142 patients with type 2 diabetes, and carried out a GST and a NMTT. We carried out the NMTT using a calorie‐controlled meal based on an intake of 30 kcal/kg ideal bodyweight/day. We calculated the change in C‐peptide immunoreactivity (ΔCPR) by subtracting fasting CPR from the CPR 6 min after the 1‐mg glucagon injection (GST) or 120 min after the meal (NMTT). Results: Mean ΔCPR for the GST was 2.0 ng/mL, and for the NMTT was 3.1 ng/mL. A total of 104 patients had greater ΔCPR in the NMTT than the GST, and the mean ΔCPR was significantly greater in the NMTT than the GST ( P < 0.05). To exclude any influence of antidiabetic drugs, we examined 42 individuals not taking antidiabetic agents, and found the mean ΔCPR was significantly greater in the NMTT than the GST (GST 2.4 ng/mL, NMTT 4.3 ng/mL; P < 0.05). To consider the influence of glucose toxicity, we carried out receiver operating characteristic analyses with fasting plasma glucose and glycated hemoglobin. The optimal cut‐off levels predicting GST ΔCPR to be larger than NMTT ΔCPR were fasting plasma glucose 147 mg/dL and glycated hemoglobin 9.0% (fasting plasma glucose: sensitivity 0.64, specificity 0.76, area under the curve 0.73; glycated hemoglobin: sensitivity 0.56, specificity 0.71, area under the curve 0.66). Conclusions: The NMTT is a reliable insulin secretion test in patients with type 2 diabetes, except for those in a hyperglycemic state. Abstract : The normal meal tolerance test is a reliable insulin secretion test in patients with type 2 diabetes, except those in a hyperglycemic state.